Solid electrolyte for lithium metal solid-state battery, preparation method and lithium metal solid-state battery

By using solid electrolytes with high ionic conductivity in lithium metal batteries, the cycle life and safety issues of lithium metal batteries are solved, and the high cycle stability and good industrial application prospects of lithium metal solid batteries are achieved.

CN119695268APending Publication Date: 2025-03-25深圳毅华新能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901686.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

During the circulation process, the cycle life and safety problems of the existing lithium metal batteries are caused by the instability of the SEI film and the formation of lithium dendrites. In addition, the traditional SEI has low ionic conductivity, poor kinetic performance and low mechanical strength, making it difficult to meet the needs of long cycle life.

Method used

A solid electrolyte including 0.3-0.5 parts of polymer matrix and 0.3-1 part of mixed salt is used. The mixed salt consists of sodium salt and lithium salt, and the molar ratio of sodium ions to lithium ions is 1:40-60. Through the combination of specific polymer matrix and salt and preparation methods, the ionic conductivity and electrochemical window of the solid electrolyte are improved.

Benefits of technology

The high ionic conductivity, excellent cycle stability and good industrial application prospects of lithium metal solid-state batteries have been achieved. The assembled lithium metal solid-state batteries can be stable for 400 cycles at room temperature 1C, with a capacity retention rate of >95%, and can still exert a capacity of nearly 140mAh/g at 2C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695268A_ABST
    Figure CN119695268A_ABST
Patent Text Reader

Abstract

The invention relates to a solid electrolyte for a lithium metal solid-state battery, a preparation method and the lithium metal solid-state battery, the solid electrolyte comprises, by mass, 0.3-0.5 part of a polymer matrix and 0.3-1 part of a mixed salt, the mixed salt is composed of a sodium salt and a lithium salt, the molar weight ratio of sodium ions in the sodium salt to lithium ions in the lithium salt in the mixed salt is 1: (40-60). The solid electrolyte disclosed by the invention has high ionic conductivity and a wide electrochemical window, a lithium metal symmetric battery participating in assembly has a high ion transference number, and a lithium metal solid-state battery participating in assembly shows excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a solid electrolyte for a lithium metal solid-state battery, a preparation method and a lithium metal solid-state battery, and belongs to the field of solid electrolytes. Background Art

[0002] With the rapid development of social economy, the excessive consumption of fossil resources such as coal, oil and natural gas has triggered an increasingly serious energy crisis and environmental pollution. The development of green and clean renewable energy has become a global consensus. Due to the discontinuity of emerging energy sources such as wind and solar energy, the development of the new energy industry is inseparable from efficient and low-cost battery energy storage systems. Since the first commercial launch of lithium-ion batteries, their extensive application in portable electronic devices and clean energy vehicles has profoundly affected our lives. However, due to the inherent limitations of the theoretical specific capacity of graphite-based negative electrodes, this type of battery cannot meet the growing demand for energy density. Therefore, there is an urgent need to develop the next generation of high energy density energy storage devices. Metallic lithium has an ultra-high theoretical capacity (3860mAh g -1 ) and extremely low electrochemical potential (-3.04V relative to standard hydrogen electrode), it is recognized as the most promising negative electrode material in high-performance lithium batteries. Lithium metal batteries composed of lithium metal as negative electrode, including lithium-sulfur batteries, lithium-air batteries and lithium-oxide batteries, have prominent advantages over lithium-ion batteries in energy density. However, before lithium metal negative electrode becomes a usable technology, huge challenges need to be overcome. First, lithium metal has high reactivity and will inevitably react with organic liquids and electrolytes, and the solid electrolyte membrane formed is easy to rupture. In addition, the formation of lithium dendrites, the continuous consumption of electrolyte, and the increase of interfacial impedance reduce the cycle life and safety of lithium metal batteries. In addition, the traditional SEI is difficult to meet the requirements of achieving long cycle life due to its low ionic conductivity, poor kinetic performance and low mechanical strength, resulting in the growth of lithium dendrites and uneven lithium deposition. At the same time, the volume of lithium metal changes during the charge and discharge process, which will cause the unstable SEI to rupture, resulting in the complete loss of the protective effect of SEI, further exacerbating the consumption of active lithium and electrolyte. At present, in order to obtain a stable and efficient lithium metal battery system, researchers have proposed strategies such as constructing an artificial passivation film on the surface of the lithium electrode, using electrolyte additives to modify the lithium electrode interface, and modifying the structure of the metal lithium negative electrode. Among the existing strategies, the technical route of using additives can avoid the complex lithium electrode pretreatment process and has the advantages of simple methods and low costs. Therefore, how to reasonably design and construct a stable SEI film is the key to achieving long-term stable operation of metal lithium batteries. Summary of the invention

[0003] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide a solid electrolyte with high ionic conductivity for lithium metal solid-state batteries; the second object of the present invention is to provide a method for preparing a solid electrolyte; the third object of the present invention is to provide a lithium metal solid-state battery.

[0004] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0005] A solid electrolyte for a lithium metal solid-state battery, wherein the solid electrolyte comprises, by mass, 0.3-0.5 parts of a polymer matrix and 0.3-1 parts of a mixed salt, wherein the mixed salt consists of a sodium salt and a lithium salt, and the molar ratio of the sodium ions in the sodium salt to the lithium ions in the lithium salt in the mixed salt is 1:40-60.

[0006] Furthermore, the molar ratio of sodium ions in the sodium salt to lithium ions in the lithium salt in the mixed salt is 1:42-58, preferably 1:45-55, and more preferably 1:48-52.

[0007] Furthermore, the sodium salt is any one or more of NaCl, NaF, NaBr, NaI, Na2SO4, NaNO3, NaPF6, NaTFSI, NaFSI, and NaDFOB.

[0008] Furthermore, the lithium salt is any one or more of LiCl, LiF, LiBr, LiI, Li2SO4, LiNO3, LiPF6, LiTFSI, LiFSI, and LiDFOB.

[0009] Furthermore, the polymer matrix includes any one or more of polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP).

[0010] Optionally, the weight average molecular weight of the polymer matrix is ​​300,000-500,000, further 350,000-450,000.

[0011] The method for preparing the solid electrolyte as described above comprises the following steps:

[0012] S1, mixing the polymer matrix, the mixed salt and the organic solvent uniformly to obtain a slurry;

[0013] Wherein, the organic solvent is DMF; the mass volume ratio of the polymer matrix to the organic solvent is 0.4g:5-12mL, preferably 0.4g:6-10mL;

[0014] S2. Casting the slurry into a film and drying it to obtain a solid electrolyte.

[0015] Further, in S1, the polymer matrix is ​​mixed with an organic solvent to obtain a polymer solution; the mixed salt is mixed with an organic solvent to obtain a mixed salt solution; and the polymer solution and the mixed salt solution are mixed to obtain a slurry. Optionally, in S2, the slurry is cast into a film with a thickness of 800-1200 μm, and then dried to obtain a solid electrolyte.

[0016] Further, in S2, vacuum drying is performed at 75-85°C for 10-14h, preferably at 78-82°C for 11-13h.

[0017] Optionally, the solid electrolyte has a thickness of 120 μm-150 μm.

[0018] A lithium metal solid-state battery comprises a positive electrode plate, a solid electrolyte as described above or a solid electrolyte prepared by the preparation method as described above, and a negative electrode plate which are stacked in sequence.

[0019] Optionally, the active material of the positive electrode plate is a conventional commercial lithium battery positive electrode material, and other components of the positive electrode plate are a conductive agent, a binder and other functional mixed salts.

[0020] Preferably, the positive electrode active material is high-capacity nickel-cobalt-manganese oxide.

[0021] Preferably, the negative electrode plate is made of lithium metal, lithium-copper composite strip or other alloyed lithium metal negative electrode.

[0022] Preferably, the thickness of the negative electrode sheet is 20-500 μm.

[0023] Compared with the prior art, the beneficial technical effects of the present invention are:

[0024] (1) The solid electrolyte of the present invention has good ionic conductivity and a wide electrochemical window. The assembled lithium metal symmetric battery has a good ion migration number. The assembled lithium metal solid-state battery has excellent cycle stability. Specifically, the ionic conductivity of the obtained solid electrolyte can reach above 1.371 mS / cm. The assembled lithium metal solid-state battery can stably cycle 400 times at room temperature at a rate of 1C, and the capacity retention rate is >95%. At a rate of 2C, it can still exert a capacity of nearly 140 mAh / g, and has good prospects for industrial application.

[0025] (2) The preparation method of the solid electrolyte of the present invention is simple, the raw materials are easily available, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison diagram of the XRD curves of the solid electrolytes in Example 1, Example 2, Example 6 and Comparative Examples 1-2 of the present invention.

[0027] Figure 2 It is a comparison chart of the infrared spectra of the solid electrolytes in Example 1, Example 2, Example 6 and Comparative Examples 1-3 of the present invention.

[0028] Figure 3 It is a graph showing the room temperature ionic conductivity test results of the solid electrolytes in Examples 1-4 and Comparative Examples 1-3 of the present invention.

[0029] Figure 4 It is a graph of room temperature electrochemical window test results of the solid electrolytes in Examples 1-4 and Comparative Examples 1-3 of the present invention.

[0030] Figure 5 This is a graph showing the room temperature ion migration number test results of the lithium metal symmetric battery assembled in Example 1 of the present invention.

[0031] Figure 6 This is a test chart of the lithium metal stability of the lithium metal symmetric battery assembled in Example 1 of the present invention at room temperature.

[0032] Figure 7 It is a schematic diagram of the room temperature cycling performance of the lithium metal solid-state battery assembled in Example 1 of the present invention.

[0033] Figure 8 It is a schematic diagram of the room temperature rate performance of the lithium metal solid-state battery assembled in Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0035] Example 1

[0036] In this embodiment, a method for preparing a solid electrolyte for a lithium metal solid-state battery comprises the following steps:

[0037] 0.4g poly (vinylidene fluoride - hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400000), 0.012g NaFSI and 0.561g LiFSI were dissolved in 6mL DMF, stirred until completely dissolved, the stirring temperature was set to 50°C, and the stirring time was 8h to obtain an electrolyte slurry. The electrolyte slurry was scraped on the mold with a scraper (the scraping thickness was 1000 microns), placed in a vacuum drying oven at 80°C and dried for 12h to remove the solvent, and a polymer solid electrolyte membrane (solid electrolyte) was obtained.

[0038] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0039] Assembly of lithium metal symmetric battery: Assemble Li||Li symmetric battery (lithium metal symmetric battery) in the order of negative electrode shell, lithium sheet, polymer-based solid electrolyte, lithium sheet, and positive electrode shell, and conduct ion migration number and lithium metal stability tests.

[0040] Assembly of lithium metal solid-state battery: Assemble the positive electrode plate, the above-mentioned solid electrolyte, and the negative electrode plate into a lithium metal solid-state battery.

[0041] The preparation method of the positive electrode is as follows: lithium nickel cobalt manganese (LiNi 0.8 Co 0.1 Mn 0.1 O2) is used as the active material, and is mixed evenly with a conductive agent (acetylene black) and a binder [polyvinylidene fluoride (PVDF, weight average molecular weight of 700000)] at a mass ratio of 80:10:10, and then coated on a carbon-coated aluminum foil to obtain a positive electrode sheet;

[0042] Selection of negative electrode sheet: 450μm thick metal lithium sheet is used as the negative electrode.

[0043] In addition, a symmetrical battery was assembled in the order of negative electrode shell, gasket (304 stainless steel, diameter × thickness: 15.6mm × 0.5mm), polymer-based solid electrolyte (SE), gasket (15.6mm × 0.5mm), and positive electrode shell, and the ionic conductivity of the solid electrolyte was tested. The battery was assembled in the order of negative electrode shell, gasket (15.6mm × 0.5mm), polymer-based solid electrolyte (SE), lithium sheet (15.6mm × 0.45mm), and positive electrode shell, and the electrochemical window of the solid electrolyte was tested.

[0044] The solid electrolyte has a high ionic conductivity of 1.371 mS / cm, and the high ion migration number of the assembled lithium metal symmetric battery is 0.53. The assembled lithium metal solid-state battery can be stably cycled for 400 cycles at 1C rate at room temperature, with a capacity retention rate of 96.73%. At 2C rate, it can still exert a capacity of nearly 140 mAh / g. The assembled Li||Li symmetric battery has a capacity retention rate of 0.1 mA / cm 2 The deposition and stripping can be stably carried out for 1200 hours at a current density of , which is of great industrial application value.

[0045] Example 2

[0046] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.012 g of NaFSI and 0.561 g of LiFSI were dissolved in 4 mL of DMF, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0047] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0048] Example 3

[0049] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.012 g of NaFSI and 0.561 g of LiFSI were dissolved in 8 mL of DMF, stirred until completely dissolved, the stirring temperature was set to 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0050] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0051] Example 4

[0052] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.012 g of NaFSI and 0.561 g of LiFSI were dissolved in 10 mL of DMF, stirred until completely dissolved, the stirring temperature was set to 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0053] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0054] Example 5

[0055] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.015 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of DMF, stirred until completely dissolved, the stirring temperature was set to 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0056] Among them, the molar ratio of sodium ions to lithium ions is 1:40.

[0057] Example 6

[0058] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.0102 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of DMF and stirred until completely dissolved. The stirring temperature was set to 50 ° C and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto the mold and placed in a vacuum drying oven at 80 ° C for 12 h to remove the solvent to obtain a polymer solid electrolyte membrane.

[0059] Among them, the molar ratio of sodium ions to lithium ions is 1:60.

[0060] Example 7

[0061] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.018 g of NaTFSI and 0.861 g of LiTFSI were dissolved in 6 mL of DMF, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0062] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0063] Example 8

[0064] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.010 g of NaPF6 and 0.456 g of LiPF6 were dissolved in 6 mL of DMF, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0065] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0066] Comparative Example 1

[0067] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and 0.561 g of LiFSI were mixed, and finally 6 mL of N,N-dimethylformamide was added, and the stirring temperature was set to 50° C. for 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, and dried in a vacuum drying oven at 80° C. for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0068] Comparative Example 2

[0069] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.012 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of N-methylpyrrolidone, stirred until completely dissolved, the stirring temperature was set to 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0070] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0071] Comparative Example 3

[0072] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.012 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of acetone, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0073] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0074] Comparative Example 4

[0075] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.017 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of DMF, stirred until completely dissolved, the stirring temperature was set to 50 ° C, and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto the mold, placed in a vacuum drying oven at 80 ° C and dried for 12 h to remove the solvent, and a polymer solid electrolyte membrane was obtained. The molar ratio of sodium ions to lithium ions was 1:35.

[0076] Comparative Example 5

[0077] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.0094 g of NaFSI and 0.561 g of LiFSI were dissolved in 6 mL of DMF and stirred until completely dissolved. The stirring temperature was set to 50 ° C and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto the mold and placed in a vacuum drying oven at 80 ° C for 12 h to remove the solvent to obtain a polymer solid electrolyte membrane. The molar ratio of sodium ions to lithium ions was 1:65.

[0078] Comparative Example 6

[0079] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and 0.861 g of LiTFSI were mixed, and finally 6 mL of N,N-dimethylformamide was added, and the stirring temperature was set to 50° C. for 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, and dried in a vacuum drying oven at 80° C. for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0080] Comparative Example 7

[0081] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and 0.456 g of LiPF6 were mixed, and finally 6 mL of N,N-dimethylformamide was added, and the stirring temperature was set to 50° C. for 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, and dried in a vacuum drying oven at 80° C. for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0082] Comparative Example 8

[0083] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and 0.431 g of LiDFOB were mixed, and finally 6 mL of N,N-dimethylformamide was added, and the stirring temperature was set to 50° C. for 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, and dried in a vacuum drying oven at 80° C. for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0084] Comparative Example 9

[0085] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.013 g of potassium bis(fluorosulfonyl)imide (KFSI) and 0.561 g of LiFSI were dissolved in 6 mL of N,N-dimethylformamide, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0086] Among them, the molar ratio of potassium ions to lithium ions is 1:50.

[0087] Comparative Example 10

[0088] Repeat comparative example 1, the only difference is: NaFSI is used instead of LiFSI. Take 0.4g polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) and 0.609g NaFSI and mix them. Finally, add 6mL N,N-dimethylformamide, set the stirring temperature to 50°C, and stir for 8h to obtain electrolyte slurry. Apply the electrolyte slurry on the mold, place it in a vacuum drying oven at 80°C and dry it for 12h to remove the solvent to obtain a polymer solid electrolyte membrane.

[0089] Comparative Example 11

[0090] Example 1 was repeated, except that 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.011 g of NaDFOB and 0.431 g of LiDFOB were dissolved in 6 mL of DMF, stirred until completely dissolved, the stirring temperature was set at 50° C., and the stirring time was 8 h to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a mold, placed in a vacuum drying oven at 80° C. and dried for 12 h to remove the solvent, thereby obtaining a polymer solid electrolyte membrane.

[0091] Among them, the molar ratio of sodium ions to lithium ions is 1:50.

[0092] Table 1 Performance test results of various embodiments and comparative examples

[0093]

[0094]

[0095] By comparing Examples 1 to 8 and Comparative Examples 1 to 11 in Table 1, it can be seen that by introducing trace amounts of sodium ions into the polymer solid electrolyte, the ionic conductivity at room temperature is significantly improved, the electrochemical window can be widened, and the ion migration number is significantly improved. Furthermore, after 400 cycles, the capacity retention rate of Example 1 is significantly higher than that of Comparative Example 1 (48.21%), reaching 96.73%. The cycle performance of other embodiments is improved. By comparison, it can also be seen that when a specific sodium salt is introduced and a certain amount of DMF is used as a solvent, it is helpful to obtain particularly outstanding ionic conductivity, ion migration number, electrochemical window and cycle performance. The possible reason is that the sodium ions have low binding energy with the DMF solvent, and their desolvation barrier is low. They interact with the PVDF chains in PVDF-HFP to produce C=C bonds and change the crystal structure of PVDF-HFP, so that the PVDF chains of some PVDF-HFP are transformed from α phase to β phase (see Figure 2 ), enhance the dissociation of lithium salts, form more free charge carriers (lithium ions), and at the same time increase the migration number of lithium ions and reduce the activation energy. The simultaneous introduction of lithium salts and sodium salts can show a synergistic effect, effectively improving the electrochemical properties such as ionic conductivity and the cycle stability of solid-state batteries. In addition, it can be seen from the comparison that the DMF solvent is too little and the performance is not ideal. The possible reason is that DMF is too little, the above-mentioned crystal structure changes are limited, and in addition, the lithium salt and sodium salt may not be completely dissolved, and the free ions in the solution are reduced. The DMF solvent is excessive, and the performance is also not ideal. The possible reason is that DMF is excessive, causing DMF to decompose prematurely, the electrochemical window to narrow, and the residual DMF in the cycle process deteriorates the interface, which seriously affects the long cycle performance of the battery. The sodium salt additive is excessive, and the performance is also not ideal. The possible reason is that excessive sodium salt causes the viscosity of the membrane solution to increase, hindering the transmission of lithium ions. The sodium salt additive is too little, and the performance is also not ideal. The possible reason is that there are fewer free sodium ions, and the effect with DMF and PVDF chains is not strong enough, and the improvement of electrochemical performance is not obvious. In addition, the performance is not ideal when introducing trace potassium ions to replace sodium ions. The possible reason is that the strong interaction between potassium ions and DMF leads to low complexation content between DMF and lithium ions, which affects the transmission of lithium ions. Thirdly, when sodium salts such as NaDFOB, lithium salts such as LiDFOB, or solvents such as N-methylpyrrolidone and acetone are used, the performance is also not ideal. See Figure 2When using solvents such as N-methylpyrrolidone and acetone, the PVDF chain does not undergo obvious phase change (α phase → β phase). Therefore, the present invention uses specific sodium salts, lithium salts, solvents and polymer matrices, and controls their usage ratios, and the obtained solid electrolyte and the assembled lithium metal solid-state battery can show very excellent performance indicators in terms of ion conductivity, ion migration number and cycle stability.

[0096] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A solid electrolyte for lithium metal solid-state batteries, characterized in that: In parts by mass, the solid electrolyte comprises 0.3-0.5 parts of a polymer matrix and 0.3-1 parts of a mixed salt, wherein the mixed salt consists of a sodium salt and a lithium salt, and the molar ratio of the sodium ions in the sodium salt to the lithium ions in the lithium salt in the mixed salt is 1:40-60.

2. The solid electrolyte according to claim 1, characterized in that The molar ratio of sodium ions in the sodium salt to lithium ions in the lithium salt in the mixed salt is 1:42-58.

3. The solid electrolyte according to claim 1 or 2, characterized in that The sodium salt is any one or more of NaCl, NaF, NaBr, NaI, Na2SO4, NaNO3, NaPF6, NaTFSI, NaFSI, and NaDFOB.

4. The solid electrolyte according to claim 1 or 2, characterized in that The lithium salt is any one or more of LiCl, LiF, LiBr, LiI, Li2SO4, LiNO3, LiPF6, LiTFSI, LiFSI, and LiDFOB.

5. The solid electrolyte according to claim 1 or 2, characterized in that: The polymer matrix includes any one or more of polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

6. The method for preparing a solid electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: S1, mixing the polymer matrix, the mixed salt and the organic solvent uniformly to obtain a slurry; Wherein, the organic solvent is DMF; the mass volume ratio of the polymer matrix to the organic solvent is 0.4g:5-12mL; S2. Casting the slurry into a film and drying it to obtain a solid electrolyte.

7. The preparation method according to claim 6, characterized in that: In S1, the polymer matrix and the organic solvent are mixed evenly to obtain a polymer solution; the mixed salt and the organic solvent are mixed evenly to obtain a mixed salt solution; The polymer solution and the mixed salt solution are then mixed evenly to obtain a slurry.

8. The preparation method according to claim 6, characterized in that: S2 was dried under vacuum at 75-85°C for 10-14h.

9. A lithium metal solid-state battery, characterized in that: It comprises a positive electrode sheet stacked in sequence, a solid electrolyte as described in any one of claims 1 to 5 or a solid electrolyte prepared by the preparation method as described in any one of claims 6 to 8, and a negative electrode sheet.